Cultural China 2020 : the contemporary China Centre review - Kehoe, Séagh; Wielander, Gerda (University of Westminster Press, 2021)
Cultural China is a unique annual publication for up-to-date, informed, and accessible commentary about Chinese and Sinophone languages, cultural practices, politics and production, and their critical analysis. It builds on the University of Westminster’s Contemporary China Centre Blog, providing additional reflective introductory pieces to contextualise each of the eight chapters. The articles in this Review speak to the turbulent year that was 2020 as it unfolded across cultural China. Thematically, they range from celebrity culture, fashion and beauty, to religion and spirituality, via language politics, heritage, and music. Pieces on representations of China in Britain and the Westminster Chinese Visual Arts Project reflect our particular location and home. Many of the articles in this book focus on the People’s Republic of China, but they also draw attention to the multiple Chinese and Sinophone cultural practices that exist within, across, and beyond national borders. The Review is distinctive in its cultural studies-based approach and contributes a much-needed critical perspective from the Humanities to the study of cultural China. It aims to promote interdisciplinary dialogue and debate about the social, cultural, political, and historical dynamics that inform life in cultural China today, offering academics, activists, practitioners, and politicians a key reference with which to situate current events in and relating to cultural China in a wider context.